Heating power effect on the thermal runaway characteristics of large-format lithium ion battery with Li(Ni1/3Co1/3Mn1/3)O2 as cathode. (15th January 2022) - Huang, Zonghou; Shen, Ting; Jin, Kaiqiang; Sun, Jinhua; Wang, Qingsong
Abstract: Overheat is one of the common safety issues for the large-scale application of lithium-ion batteries (LIBs), and is a potential risk that triggers thermal runaway (TR). In this work, the effects of the heating power and state of charge (SOC) on TR characteristics of large-format (Ni1/3 Co1/3 Mn1/3 )O2 LIBs under overheat are investigated experimentally. The relationship between heating power, critical input thermal energy ( E input ) and TR are identified firstly. The results show the E input, critical internal energy, chemical heat and joule heat of batteries in critical TR state all decrease with increasing SOC. The heating power exhibits more significant impact on TR behavior than SOC dues to the rapid deterioration of TR as heating power ascends. The peak heat release rate of TR rises from 7.5 to 95.2 kW when heating power increases from 400 to 700 W. And the law the severity of TR deteriorates sharply with increasing heating power is more prominent in the TR propagation process. Besides, TR induced by higher heating power requires lower E input . E input decreases from 477.08 to 329.23 kJ as heating power ascends from 400 to 700 W. Furthermore, the relationship between internal short circuit and TR under different SOC and heating power are analyzed. Graphical abstract: Image 1 Highlights: Thermal runaway feature of lithium ion battery induced by overheat is investigated. Relationship between heating power and critical input thermal energy is identified. Thermal runaway deteriorates significantly with increasing heating power. Thermal runaway under higher heating power need lower critical input thermal energy. Relationship between internal short circuit and thermal runaway is revealed.